Antimicrobial Efficacy of Dental Materials Modified with Biosynthesized Silver Nanoparticles: A Review - Naidu, Madhavi; Sabrish, Sharanya; Shivamurthy, Prashantha G; Sagarkar, Roshan M (Journal of Orofacial Research, 2024)
Background: Silver metal alloy has been used by dentists for more than 150 years in hundreds of millions of patients. It is the most thoroughly researched and tested of all the dental materials. Its antimicrobial property is attributed to sustained ion release. With advent of nanotechnology increased number of research on dental material containing Silver nanoparticles have proven the antimicrobial efficacy of the same. However the reduction of the Silver metal salts with chemicals pose a threat on the environment in the long term. Hence there is a growing trend towards green or biosynthesis of the Silver nanoparticles using microbe mediated or plant mediated reduction process. Aim: This paper reviews the antimicrobial efficacy of the silver nanoparticles which were biosynthesized in prevention of dental infections when used with materials used in dentistry. Methodology: The literature search was performed in PubMed using the Silver nanoparticles, biosynthesized, green synthesis, antimicrobial effect, dentistry. Only full text articles from 2013 to 2023 were considered. Results: The search retrieved 16 articles which were screened per exclusion criteria of removing duplicate studies, six articles were selected for review. Conclusion: Biosynthesized Silver nanoparticles are proven to be effective against Gram Positive, Gram Negative causing dental infections when used in conjunction with conventional dental materials.